Abiding nourishment: vegetable production and the pursuit of nutritional sovereignty in Colorado - McCollum, Sean C., author; Little, Ann, advisor; Childers, Michael, committee member; Martinez, Doreen, committee member (Colorado State University. Libraries, 2021)
This thesis explores the various methods of small-scale gardening efforts and the importance of wild and cultivated plant food to the people who have inhabited Colorado. From Arapaho and Cheyenne horticultural practices to the kitchen gardens of the American homesteader, and the vegetable truck of the first generation of Coloradan-Americans, the environment of the Rocky Mountains forced its inhabitants to adapt their methods of planting vegetables and fruit in order to survive. The pursuit of nutritious plant food is the central human-scale endeavor in Colorado's diverse history. This thesis explores the nutritional content of several important vegetables and fruits, their importance to Colorado's inhabitants, and how the environment of Colorado lends itself to the cultivation of fruits and vegetables, while challenging the planter to a nearly extreme degree.
Keywords: food history; horticulture; nutrition; homestead; Colorado; Indigenous